Enhancement in the performance of ultrathin hematite photoanode for water splitting by an oxide underlayer - Grätzel, Michael (2013)
A 2-nm thick Nb2O5 underlayer deposited by atomic layer deposition increases the charge separation efficiency and the photovoltage of ultrathin hematite films by suppressing electron back injection. Absorbed photon-to-current efficiencies (APCE) as high as 40%, which are one of the highest ever reported with hematite photoanodes, are obtained at 400 nm at +1.43 V vs. RHE.